TANTANGAN ILMU-ILMU KEISLAMAN DI TENGAH PERKEMBANGAN ILMU PENGETAHUAN MODERN - Rizka Amelia Armin (Jurnal Commercium: Kajian Masyarakat Kontemporer, 2019)
AbstractOne important aspect to find out the secret behind the universality of Islam is the urge to seek knowledge anywhere and anytime. With the encouragement of the verses of the Qur'an which advocates for Muslims to appreciate the power of reason and the teachings of the prophet Muhammad to always seek knowledge. Islamic sciences are the sciences that are developed by Muslims, both physical and metaphysical knowledge that are bound to Islamic teachings. Islamic science is a science that has spiritual and intellectual meaning. While modern science, are the sciences developed by western scientists who are built on rational thought, regardless of philosophical or religious (secular) rules. Awareness of the underdevelopment of Islamic sciences towards the West arises because in developing knowledge among Muslims so far there are still many uses of deductive logic. Among Islam there are still many that emphasize literature study rather than the study of socio-cultural reality and the absence of a clear paradigm of the position of normative values, the existence and structure of Islamic science.